Cowards Don't Make History : Orlando Fals Borda and the Origins of Participatory Action Research - Rappaport, Joanne (Book collections on Project MUSE., 2020)
"COWARDS DON'T MAKE HISTORY examines the contributions of Orlando Fals Borda, Juana Julia Guzmán, and Ulianov Charlaka to the early development of participatory action research in the field of sociology. These Colombian activist-researchers developed participatory action research, which upholds active participation from the communities of inquiry, in order to erase distinctions between researcher and researched, encourage dialogue between academic knowledge and the people's knowledge, and transform research into a political organizing tool. COWARDS DON'T MAKE HISTORY connects Fals Borda's work in the 1970s and 1980s to present ethnographic methods. In addition to its social scientific inquiry into the everyday practices and dynamics of Fals Borda's Fundación del Caribe (the activist collective that Fals founded to produce research useful to campesino or peasant leadership), the study interrogates the manner in which the Fundación and La Rosca refigure historical methods in activism. COWARDS DON'T MAKE HISTORY demonstrates the importance of social science that emerges from the Global South and the challenge that the methodologies of Latin American social scientists pose towards Western Academic modes of research and writing. The book begins with the historical context of the Caribbean coast in the twentieth century, detailing the various moments at which campesino organizing disrupted the spread of capitalism. Chapter 1 also introduces readers to the work of the Fundación del Caribe. Chapter 3 explores how the Fundación del Caribe resignified "participation" and "research" in a region whose peasants were largely illiterate, living hand-to-mouth, and with limited access to other parts of Colombia. Chapter 5 examines the practices that encouraged peasant participation in workshops. In the concluding chapter, Rappaport employs some of the participatory action techniques in order to argue that Fals Borda is a living legacy whose work as a teacher, writer, and activist remains relevant in Colombia's contemporary moment"--